The application of reader-response theory to teach symbolism in literature class for EFL students - Putri Rindu Kinasih (Journal of Research on English and Language Learning (J-REaLL), 2020)
For years, scholars believed one effective approach that can be used in teaching literature in EFL context is reader-response approach yet very limited study can be found about the application of reader-response theory in teaching symbolism. Whereas, symbolism is considered as the most important elements of serious imaginative literature which provide rich sources of insight. The problem is, deciding exactly what is represented by a symbol is not an easy thing to do, though the general meaning is clear because a symbol most commonly represents something unnamed. This research aimed to find out the application of reader-response theory in teaching symbolism. This research observed 16 participants majoring in English Literature program. Within four weeks, the participants were asked to read selected poems and short stories and asked to write a reflective writing as a response. Then, the writings were assessed by using critical thinking rubric. From this research, it can be drawn that the participants’ score of symbolism interpretation were increasing by the end of the research. In other word, reader-response theory is beneficial to the improvement of students’ inadequacies in studying symbolism and offers potential benefits to solve problems in literature discussion such as low self-confidence and fear of stating out different interpretations. By the end of the research, the participants are more accustomed to express various ideas and more motivated to explore more supporting sentences to strengthen their ideas.